Temperature Threshold and Water Role in CVD Growth of Single-Walled Carbon Nanotubes - Geng, Junfeng; Motta, Marcelo; Engels, Volker; Luo, Jikui; Johnson, Brian F. G. (Frontiers in Materials, 2016)
An in-depth understanding of the growth process of single-walled carbon nanotubes is of vital importance to the control of the yield of the material and its carbon structure. Using a nickel/silica (Ni/SiOx) catalyst, we have conducted a series of growth experiments with a chemical vapor deposition (CVD) system. We find that there is a temperature threshold in the CVD process, and if the reaction temperature sets above this threshold, there will be no growth of the nanotubes. Moreover, we find that in association with this temperature effect, water plays an important role in the promotion or termination of the growth of single-walled carbon nanotubes.